Transformation of Islamic Religious Education in Facing the Challenges of Sharia Economics - Nur’aiun Gulo; Hazrulta Aulia (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
This study aims to analyze the transformation of Islamic Religious Education (PAI) in addressing the challenges of Islamic economics in Labuhanbatu Regency. The rapid development of Islamic economics requires human resources who not only possess religious understanding but also have economic competencies based on Islamic values. This study employed a qualitative approach with a descriptive method. Data were collected through interviews, observations, and documentation conducted at Islamic educational institutions in Labuhanbatu Regency. Data analysis was performed using the interactive model of Miles, Huberman, and Saldaña, consisting of data collection, data condensation, data display, and conclusion drawing. The results indicate that the transformation of Islamic Religious Education is carried out through the development of an Islamic economics-based curriculum, innovation in learning methods, improvement of teacher competencies, and strengthening of students’ Islamic economic literacy. However, the implementation of this transformation still faces several challenges, including limited teachers’ understanding of Islamic economics, the lack of optimal integration of Islamic economic materials into the curriculum, and limited relevant learning resources. This study emphasizes that the transformation of Islamic Religious Education plays a strategic role in developing a generation that is religious, competent, and capable of supporting the sustainable development of the Islamic economic ecosystem.